Tanzania’s Compliance to International COVID-19 Standards: Determinants and Extent - Tairo, Maria; Francis, Boniphace (Tanzania Journal of Sociology, 2025)
This article assesses Tanzania’s level of compliance to international COVID-19 preventive measures, with a focus on the political, economic, and socio-cultural factors that influenced the adherence. A qualitative research approach with descriptive design were adopted. Data were collected through semi-structured interviews with 28 purposively selected participants, including healthcare workers and government officials from Dar es Salaam and Dodoma. Moreover, relevant documents from health sector were reviewed. Thematic analysis was performed using Computer-Assisted Qualitative Data Analysis Software (CAQDAS). The findings revealed that political leadership played a pivotal role in shaping compliance levels. The 5th regime demonstrated skepticism toward WHO guidelines and promoted traditional remedies, while the 6th regime re-engaged with international protocols and endorsed vaccination. Economically, Tanzania’s dependence on informal employment, which accounts for approximately 76% of the workforce, hindered the implementation of strict lockdowns, as economic survival took precedence. Additionally, limited health infrastructure and a shortage of resources adversely affected compliance, especially in rural areas where traditional healing methods were prevalent. Tanzania’s COVID-19 response balanced public health with economic and political realities amid political transition and cultural factors. The study recommends expert-led communication, health system investments in diagnostics and rural care, culturally tailored outreach to improve future pandemic preparedness.